UKRAINE MOBILE OPERATORS DEVELOPMENT STRATEGIES - Одарченко, Р.С. (Science-based technologies, 2015)
This paper analyzes the main problems of the modern cellular networks in Ukraine, including the limited frequency resources and imperfect legislation. A scenario deploy LTE networks with a view to ensuring the requirements for application of the principles of technological neutrality and refarming radio frequency resources in Ukraine. The proposed recommendations to ensure the continued development of cellular networks with the ability to maximize profits from the networks of old and new generations. The use of the concept of Single RAN to save investment costs of mobile operators in the long term, outlining the main advantages of this approach. Directions for future research related to the deficiencies of the existing networks of the third and fourth generations to realize the network 5G.